Determinantes do crédito consignado e da inadimplência de pessoas físicas no Brasil (2004-2016): uma análise com variáveis macroeconômicas - Schuh, Aline Beatriz (2017)
The Payroll Loan is a relatively recent type of loan in the Brazilian credit market, and therefore the mechanisms of its concession and its effects on the default rate of individual clients are still rather unknown. In this sense, this study aims to verify the relationship between payroll loans and macroeconomic variables, such as the Gross Domestic Product (GDP), consumption, inflation rate, unemployment, and interest rate, as well as the relationship between these and the default rate in the personal loan portfolio, between 2004 and 2016. This was accomplished through bibliographical and documentary researches, and by using two Vector Error Correction models, which enabled the calculation of the impulse response functions, the variance decomposition and the Granger causality. The results showed that the payroll loan portfolio expanded significantly over the years and its concession reacts positively to changes in the GDP, and negatively to changes in consumption, unemployment, inflation and interest rates. In addition, it was also verified that the expansion of the payroll grating contributed to mitigate the context of default, since the estimates indicated negative long-term relationships between payroll and the default rate of individual clients. It was also observed that the most significant increases in the default rates coincided with moments of economic instability in Brazil, and this was confirmed by the econometric modeling, since the results showed that the default rate reacts negatively to variations in the GDP. On the other hand, the unemployment rate, the interest rate and inflation showed positive long-term relationships with the default rate in the personal loan portfolio, and for the consumption variable, the results were inconclusive. It is noteworthy that, except for the consumption index, all other relationships were in agreement with the literature and the expected behavior, confirming, therefore, that the macroeconomic scenario played an important role in the performance of the payroll portfolio in the period, and that this type of credit contributed to mitigate default rates.